Juridical Analysis of the Validity of Share Ownership and the Implementation of Unlawful Acts in Limited Liability Companies (Study of Supreme Court Decision Number 2669 K/Pdt/2025) - Syifa Aulia Dewinta Rustama; Tri Lisiani Prihatinah (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2026)
Limited Liability Companies as a legal entity based on capital partnerships place shares as the main instrument in determining ownership structures, control rights, and legitimacy in decision-making, so that share ownership disputes have the potential to cause complex legal problems, including unlawful acts. This study aims to analyze the validity of ownership and transfer of shares through testing the complementary relationship between the PT Law and the principle of civil proof, as well as analyzing the application of unlawful acts by methodologically separating the legal standing layer and the material elements of PMH along with the responsibility of the company's organs in protecting the rights of shareholders, in the Supreme Court Decision Number 2669 K/Pdt/2025. The method used is normative legal research with a legislative approach and a case approach. The results of the discussion show that the relationship between the PT Law and the Civil Code in the context of proving share ownership is complementary, not a normative conflict that is resolved through the principle of lex specialis, and that the implementation of PMH requires a strict separation between the legal standing test as a formal requirement and the material elements of PMH. Moreover, the Supreme Court's decision reflects the choice of legal certainty values that are valid but do not fully integrate the Radbruch triadic balance between justice, utility, and legal certainty. It is recommended that the parties ensure the validity of the documents and the listing of shares, and that lawmakers consider more explicit provisions regarding the evidentiary power of stock documents in civil disputes.